EKONOMI HIJAU, PRODUKSI BERSIH DAN EKONOMI KREATIF: PENDEKATAN MENCEGAHAN RESIKO LINGKUNGAN MENUJU PERTUMBUHAN EKONOMI BERKUALITAS DI PROVINSI BALI - Yasa, I.G.W. Murjana (Bumi Lestari; Vol 10 No 2 (2010), 2010)
This article aims to look at how market failure can lead to pollution of the turn, cause high costs and how cleaner production program and the creative economy can ensure the improvement of quality of economic growth through green economy with the calculation of Green GDRP performance. This article was written based on information obtained through various sources, environmental journals, teksbook, and some of the research. From the conclusion of this article can be known that market mechanisms fail to prevent environmental risks as a result of failures in the prevention aspect of externalities, public goods and goods the ownership of common property. Implementation of the green economy, in the short term will impact the decline in economic growth, but in the long term economic performance measurement approach green GDRP will impact on the improvement of sustainable environmental quality. Implementation of cleaner production that are more preventive in preventing environmental risks and synergy with the creative economy program will be able to more quickly improve the quality of economic growth through green economic approach. Synergy of four pillars in a participatory manner is necessary in the implementation of a green economy that supported the cleaner production program and the creative economy is the government, business, academic, and community.
Keywords: green economy, risk environment, cleaner production, creative economy